Synergy Analysis Of The Goverment And Baznas Poverty Treatment Policy ( Case Study Of Bogor District) - Anita Afandi, Elvi; Yasid, Mukhamad; Taufiq Possumah, Bayu (CV. Inara, 2021)
PK policies in Bogor Regency, to analyze the role of BAZNAS and its potential and to analyze the synergy between local government policies and BAZNAS in the PPK Program. This qualitative research uses the analysis method